PENGGUNAAN NAMA DIRI MASYARAKAT BUGIS - Syamsu Rijal (Retorika, 2017)
This study describes the comparison between the proper name in the Bugis language with name nonlanguage Bugis and the factors that influence the naming of the Bugis community. Data collected through observation with note technique. The data collected were analyzed descriptively. The names of the Bugis have equivalents in other languages. There are seven factors that influence the selection process on behalf Bugis society, namely: (1) religion, (2) trends, (3) pride, (4) prestige, (5) heredity, (6) retention of identity, and (7) conditions or circumstances.